Planetesimals early differentiation and consequences for planets - Elkins-Tanton, Linda T.; Weiss, Benjamin P. (Benjamin Paul) (Cambridge planetary science, 2017)
Processes governing the evolution of planetesimals are critical to understanding how rocky planets are formed, how water is delivered to them, the origin of planetary atmospheres, how cores and magnetic dynamos develop, and ultimately, which planets have the potential to be habitable. Theoretical advances and new data from asteroid and meteorite observations, coupled with spacecraft missions such as Rosetta and Dawn, have led to major advances in this field over the last decade. This transdisciplinary volume presents an authoritative overview of the latest in our understanding of the processes of planet formation. Combining meteorite, asteroid and icy body observations with theory and modelling of accretion and orbital dynamics, this text also provides insights into the exoplanetary system and the search for habitable worlds. This is an essential reference for those interested in planetary formation, solar system dynamics, exoplanets and planetary habitability